PENGARUH BESARAN MODAL TERHADAP PEROLEHAN LABA UMKM KOTA SAMARINDA. - Achmad Rudzali; Sucipto Sucipto; Muhammad Darjad (Politeknik Negeri Samarinda, 2021)
The UMKM are a pillar of the Indonesian people's economy, especially during a period of pandemic like now. The government always efforts be together with this business group were proven by an injection of capital to make UMKM always grow and develop. Nevertheless, UMKM are still deemed not optimal in terms of management in running their businesses. One of the obstacles is the financial report, where the government was very concerned about providing capital assistance, but it was expected that it was minimal in the case of mis-targeted assistance.The spotlight was on the culinary field of UMKM, where the researcher just wanted to got an idea of whether the capital factor initiated by the government was able to increased profits for business actors? From observations to 73 MSME entrepreneurs who do culinary business using regression analysis tools, some information was obtained from UMKM. Data were taken from 4 sub-districts located in several areas of Samarinda city with an area of 103.78 km2. The average initial capital for UMKM in the Samarinda areas were around IDR 30,139,000. While the profit they get a month approximately IDR 13,324,000. From the tests conducted, the relationship between capital and profit was quite strong, amounting to 87.66%. While the percentage of influence on profits were around 76.86%, while 23.16% were the influenced by other factors such as strategies to maintain sales turnover which were aligned with the current digital era. From the analysis, it was also found that the effect of the amount of capital on the profit of UMKM in Samarinda was positive and significant. Keywords: UMKM, culinary, regression, capital, profit